Pemberdayaan Wanita Untuk Meningkatkan Jiwa Entrepreneurship di Kelurahan Jombang Kecamatan Ciputat - Sutariyonossi Sutariyonossi; Adhy Firdaus; Joned C Saksana; Muhammad Arief Noor; Tohiroh Tohiroh; Siti Mulasih; Asep Surya Lesmana; Hendra Canda; Melati Puspita Hakim; Delima Indah Permatasari; Nabila Akmas; Isnaeni Muharrifah (BADAN PENERBIT STIEPARI PRESS, 2021)
This community service aims to empower women in Jombang Village, Ciputat District, by increasing the spirit of entrepreneurship through training and mentoring programs during November 2021. Women from various age and educational backgrounds are involved in this activity. The methods used include business skills training, entrepreneurship workshops, motivational sessions, and ongoing mentoring. The training covers small business management, marketing, and financial management, while the workshop focuses on developing business ideas, business planning, and digital marketing strategies. Motivational sessions increase participants' confidence, and ongoing mentoring provides support to apply the knowledge gained. The results of the activity showed a significant improvement in the business knowledge and skills of the participants, who managed to develop innovative business ideas and start small businesses. They also demonstrated improved financial management and marketing skills, helping them manage their businesses more effectively. This program has a positive impact on the economic well-being of individual participants and the local economy. Increasing the spirit of entrepreneurship among women is expected to create more job opportunities and improve the welfare of families and communities. The implications of the activity include economic empowerment, increased independence, and strengthening the role of women in society. Appropriate support enables women to be effective agents of change, so these empowerment programs need to be continuously supported and developed for the sustainability of their positive impact.